RETRACTED: Investigating the Role of Education, Foreign Investment, and Economic Development for Sustainable Environment in BRI Countries: Application of Method of Movements Quantile Regression - Yan, Yong; Zhou, Jianhua; Zhou, Shiqi; Rao, Daokai; Zhou, Jie; Fareed, Zeeshan (Frontiers in Environmental Science, 2022)
Environmental pollution comes from several sectors of activities. It is almost conceivable that the education sector subsidies to the disruption of the environmental quality. The study employs panel cointegration techniques and Method of Moments Quantile Regression (MMQR) to inspect the influence of income, education (scholarly enrolment and expenditure), and foreign direct investment on carbon dioxide (CO2) emissions for a panel of 46 Belt and Road initiative (BRI) countries spanning the period 1996-2016. The estimation shows that the hypothesis of environmental Kuznets is established for both models. Using FMOLS, DOLS, and FE-OLS, long-run elasticities show that real income increases emissions. At the same time, foreign direct investment and education contribute to decreasing emissions in the long run. Using the approach of MMQR, the estimated coefficients confirm that only economic growth positively affects pollution growth. However, education and foreign direct investment negatively influence CO2 emissions with different quantiles levels. As policy recommendations, governments of the BRI region should improve educational service by installing new technologies, equipment, and supplies, which leads to mitigating emissions levels.